A systemic approach to the prevention and management of the causes of Hotel Environmental Sustainability Strategy Execution Failure (HESSEF) - Migale, Gilbert Harvey (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.